Cellular Changes Consistent With Epithelial–Mesenchymal Transition and Fibroblast-to-Myofibroblast Transdifferentiation in the Progression of Experimental Endometriosis in Baboons. (October 2016) - Zhang, Qi; Duan, Jie; Olson, Mark; Fazleabas, Asgerally; Guo, Sun-Wei
We have recently shown that platelets play important roles in development of endometriosis and proposed that endometriotic lesions are essentially wounds that undergo repeated tissue injury and repair (ReTIAR). Further investigation indicated that endometriotic lesions, stimulated by platelet-derived transforming growth factor β1 (TGF-β1), activate the TGF-β1/Smad3 signaling pathway and undergo epithelial–mesenchymal transition (EMT) and fibroblast-to-myofibroblast transdifferentiation (FMT), resulting in increased cellular contractility and collagen production and increased smooth muscle metaplasia (SMM), leading to fibrosis. Using serially dissected endometriotic tissue samples from baboons with induced endometriosis, we tested the hypothesis of progressive EMT, FMT, SMM, and fibrosis through TGF-β1/Smad activation using immunohistochemistry and immunoflurescence staining analyses. We found that platelets are aggregated in endometriotic lesions, and vimentin expression was increased in the epithelial compartment of the lesions as they progressively developed. We also found that the number of smooth muscle cells (SMCs) appeared to increase with time as lesions progressed and was concomitant with the increased vimentin-positive glandular epithelial cells in the lesions. As lesion development progressed, TGF-β1 and phosphorylated-Smad3 staining was elevated and the number of α-smooth muscle actin-positive myofibroblasts and highly differentiated SMCs increased in the stromal compartment, which correlated with the increasing extent of fibrosis. These results, taken together, provide support for the notion that ReTIAR occurs in the endometriotic lesions, resulting in EMT and FMT, leading to SMM and ultimately fibrosis as lesions progress. Consequently, our data also provide corroborative evidence that platelets drive the EMT and FMT in endometriotic lesions over time, promoting SMM and resulting ultimately in fibrosis in the endometriotic lesions. These findings cast a new light on the natural history of endometriosis which so far has been elusive.